Production of dengue virus-induced macrophage cytotoxin in vivo. - Gulati, L. (1986)
We have observed that dengue virus-induced cytotoxic factor (CF) induces peritoneal and splenic macrophages in vitro to produce a cytotoxin (CF2). This study demonstrates also production of CF2 in vivo in DV-infected mice and following inoculation with CF. The cell-type responsible for CF2 production in vivo is the macrophage (M phi) as M phi-depleted mice failed to produce CF2. CF2 activity could not be observed in the serum or peritoneal fluid though it is produced in peritoneal M phi. Once stimulated, CF2 is present for 4 h in M phi. M phi can be restimulated to produce CF2 only after a refractory period of 48 h.